PERAN BOOKLET TERHADAP PENGETAHUAN, SIKAP, PERILAKU JUMANTIK-PSN DAN KEBERADAAN JENTIK DI PANARUNG, KOTA PALANGKA RAYA - Natalansyah Natalansyah Natalansyah (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2019)
Objective: Dengue Haemorrhagic Fever (DHF) is one of the most contagious diseases and is a major public health problem in Indonesia. Incidence Rate of DHF in Palangka Raya city fot three years continues to increase  become 62,7% and case fatality rate 1,23% in 2016, this is because of community participation as Juru Pemantau Jentik–Pemberantasan Sarang Nyamuk (Jumantik-PSN) has not been implementes optimally. One of the strategic steps in optimizing the community participation in the control of DHF is empowerment of students with Booklet to improve the behavior of Jumantik-PSN school children. This study aim to determine the effectiveness of the use of booklets in increasing the knowledge, attitude, behavior of jumantik-PSN in school children and the presence of larvae in SDN 1 and 2 Panarung Palangka Raya City. Method: This research uses two group pre-posttest design experimental design. The sample was 60 students of fifth grade elementary school, each of 30 experimental and control groups, the instrument used by the questionnaire, the checklist, the booklet. Result: There were differences score of knowledge and attitude between control group and intervention group (P = 0,002 and P = 0,031), mann whitney test analysis there were difference of behavior score (p = 0,014) and chi square test showed different proportion of larva between the intervention group and the control group (P = 0.004). Discussion: Sismantik is the empowerment of elementary school students. Counseling with booklets significantly helped to increase the knowledge, attitude and behavior of Jumantik-PSN of school children. Conclusion:  Booklet can be one of education media alternative to convey information relating Jumantik-PSN school children so that can help improve knowledge, attitude, behavior and decrease the existence of larva.